(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In designing of clothes for pregnant women important factor is the account of features of anthropometric data changes, depending on the period of pregnancy. Clothes for pregnant women should have a rational constructive solution taking into account properties of used polimeric materials.